Las marcas de distribuidor y el derecho de la competencia en el Ecuador - Hurtado Angulo, Lenín (2016)
Brands represent a fundamental tool in the course of trade and, as a result in economic competition, very recently in the Ecuador brands ceased to be a form to establish the business origin and constituted only in a form of identifying products and services on the market, all led by the rise of the supermarkets as a way of dispensing products. Such channels of distribution managed a huge level of penetration in the market of retail sale of food, reason by which today is the main mechanism of offer and purchasing such products. Is in this scenery that they acquire a dominant position and, according to our criteria, they have abused of such position, in contrast to rules in defense of the competition, setting up even a tolerated competition unfair